A Forever War? Rethinking the Temporal Scope of Non-International Armed Conflict. (16th December 2020) - Derejko, Nathan
Abstract: How do we know when a Non-International Armed Conflict (NIAC) is over? What does International Humanitarian Law (IHL) say about its temporal scope of application during NIAC? In practice, identifying the end of a NIAC can prove exceptionally difficult. In part, this is the result of the complex spectrum of factors that contribute to the existence and continuance of NIAC, and in particular the objectives that underpin and propel a NIAC. In addition, the virtual silence of IHL regarding its temporal scope of application adds another layer of complexity to identifying the end of a NIAC. While considerable research has focused on IHL's threshold of activation during NIAC, much less attention has been given to its threshold of termination. However, the looming threat of the so-called 'forever war' has stimulated fresh interest in determining when and how NIACs (legally) end. This article provides a forensic examination of the temporal scope of IHL during NIAC, with an exclusive focus on IHL's threshold of termination. It examines two of the leading approaches for determining the temporal scope of NIAC, and argues that neither approach is entirely satisfactory, and as a result, advances and explores a novel alternative—a 'functional approach' for determining IHL's threshold of termination during NIAC.